INFLUENCE OF DECEPTIVE ADVERTISEMENTS ON CONSUMERS’ PURCHASE DECISION OF COSMETIC PRODUCTS AMONG RESIDENTS IN ILORIN, NIGERIA - SULEMAN, Abubakar Sidiq; OLORUNMOLA, Tope Joseph; MOHAMMED, Rufai Bako; AKANDE, Hameedat Doyinsola; AJIJOLA, Bashir Amoda (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2025)
This study examines the influence of deceptive advertisements on consumers' purchase decisions. The objective is to find out if consumers in Ilorin have been exposed to deceptive advertisements and if such advertisement influences their purchasing decisions. Social judgment theory was used to support the relevance of the study on how consumers assess compelling messages before buying a product. A survey method was used and 150 respondents were selected from the study area; Surulere, Agbo Oba, and Adewole all in Ilorin metropolis. Deceptive advertisement is frequently encountered by respondents, with a notable average indicating that most individuals experience it every week. Social media serves as the primary communication channel through which respondents encounter deceptive advertisements, followed by radio and blogs. The frequent exposure to deceptive advertisements across social media, radio, and blogs indicates that such advertisements are both pervasive and repetitive. Furthermore, consumers' perceptions of deceptive advertising reveal a predominantly negative viewpoint, as the majority of respondents indicated that such advertisements exaggerate benefit claims, frequently employ misleading images or videos, engage in unfair comparisons with competitors, and utilize fraudulent celebrity endorsements. The study revealed that the pervasive and repetitive nature of deceptive advertising, along with negative consumer perceptions, resulted in a decline in trust and confidence in advertised products and services, ultimately influencing purchase decisions. The study concluded that consumers’ purchase decisions will continue to reduce if communication platforms such as social media, radio and blogs are deceptively used to promote a product. It was recommended that advertisers and advert regulatory bodies should ensure advertisement ethics are upheld for a positive perception of a product by consumers to increase the purchase decision.